Comparative effectiveness of transvaginal repair vs. hysteroscopic resection in patients with symptomatic uterine niche - Xia, Wei; Wang, Xiaofeng; Wang, Yang; Tian, Yuan; He, Chuqing; Zhu, Chenfeng; Zhu, Qian; Huang, Hefeng; Shi, Liye; Zhang, Jian (Frontiers in Surgery, 2023)
Objective: To compare the efficacy of transvaginal repair and hysteroscopic resection in improving niche associated postmenstrual spotting. Methods: The improvement rate of postmenstrual spotting in women who underwent transvaginal repair or hysteroscopic resection treatment was assessed retrospectively in patients accepted at the Niche Sub-Specialty Clinic in International Peace Maternity and Child Health Hospital between June 2017 and June 2019. Postoperative spotting symptom within one year after surgery, pre- and postoperative anatomical indicators, women’ satisfaction with menstruation and other perioperative parameters were compared between the two groups. Results: 68 patients in the transvaginal group and 70 patients in the hysteroscopic group were included for analysis. The improvement rate of postmenstrual spotting in the transvaginal group at the 3rd, 6th, 9th, and 12th months after surgery was 87%, 88%, 84%, and 85%, significantly higher than 61%, 68%, 66%, and 68% in the hysteroscopic group, respectively (P<0.05). The total days of spotting improved significantly at the 3rd month after surgery but did not change over time within one year in each group (P>0.05). After surgery, the disappearance rates of the niche are 68% in transvaginal group and 38% in hysteroscopic group, however, hysteroscopic resection had shorter operative time and hospitalization duration, less complications, and lower hospitalization costs. Conclusion: Both treatments can improve the spotting symptom and anatomical structures of uterine lower segments with niches. Transvaginal repair is better in thickening the residual myometrium than hysteroscopic resection, however, hysteroscopic resection has shorter operative time and hospitalization duration, less complications, and lower hospitalization costs.